2019
DOI: 10.1126/sciimmunol.aaw8405
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell–synthesized coagulation factor X dampens antitumor immunity

Abstract: Immune evasion in the tumor microenvironment (TME) is a crucial barrier for effective cancer therapy, and plasticity of innate immune cells may contribute to failures of targeted immunotherapies. Here, we show that rivaroxaban, a direct inhibitor of activated coagulation factor X (FX), promotes antitumor immunity by enhancing infiltration of dendritic cells and cytotoxic T cells at the tumor site. Profiling FX expression in the TME identifies monocytes and macrophages as crucial sources of extravascular FX. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(166 citation statements)
references
References 70 publications
4
146
0
Order By: Relevance
“…Subsequently, full-text version of all abstracts were retrieved to assess whether inclusion criteria were met for inclusion in the qualitative assessment. To include also the most recent studies, the search strategy was repeated in PubMed and EMBASE on the 7th of October 2019, yielding three additional records with a publication date in 2019 [23][24][25].…”
Section: Search Strategy and Selection Of Papersmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, full-text version of all abstracts were retrieved to assess whether inclusion criteria were met for inclusion in the qualitative assessment. To include also the most recent studies, the search strategy was repeated in PubMed and EMBASE on the 7th of October 2019, yielding three additional records with a publication date in 2019 [23][24][25].…”
Section: Search Strategy and Selection Of Papersmentioning
confidence: 99%
“…n.descr., not described in paper; no., number; i.p., intraperitoneal; i.v., intravenous; s.c., subcutaneous. [29][30][31][32], two studies reported on rivaroxaban (both 2019) [24,25], and one study reported on both dabigatran etexilate and rivaroxaban (2019) [23].…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations